2010
DOI: 10.2139/ssrn.1646929
|View full text |Cite
|
Sign up to set email alerts
|

Group Contests with Complementarities in Efforts

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 63 publications
1
1
0
Order By: Relevance
“…They showed that if individual costs are specific nonlinear functions of individual efforts, then all group members contribute in proportion to their valuations and free-riding is reduced. Similar behaviour is predicted for the CES impact function [101,134]. In the case of weak-link contests, analysis predicts multiple equilibria including those with no free-riding at all [135].…”
Section: (Ii) Heterogeneous Groupssupporting
confidence: 61%
“…They showed that if individual costs are specific nonlinear functions of individual efforts, then all group members contribute in proportion to their valuations and free-riding is reduced. Similar behaviour is predicted for the CES impact function [101,134]. In the case of weak-link contests, analysis predicts multiple equilibria including those with no free-riding at all [135].…”
Section: (Ii) Heterogeneous Groupssupporting
confidence: 61%
“…Kolmar and Rommeswinkel (2010) further study group contests employing a constant elasticity of substitution group impact function, which allows the impact function of a group to become a perfect-substitute type or a weakest-link type with different degree of complementarity accordingly to the elasticity of substitution of efforts within the group. In the current paper we study a group contest with a best-shot group impact function, where individual group members exert costly efforts simultaneously and independently, but only the highest effort within each group represents the group effort.…”
Section: Analyzes a Group Contest With The Weakest-link Group Impact mentioning
confidence: 99%